Oncolytic varicella-zoster virus engineered with ORF8 deletion and armed with drug-controllable interleukin-12 - Stephen J Russell; Haifei Jiang; Rebecca Nace; Talia Fernandez Carrasco; Lianwen Zhang; Kah Whye Peng (Journal for ImmunoTherapy of Cancer)
Background The varicella-zoster virus (VZV), belonging to the group of human α-herpesviruses, has yet to be developed as a platform for oncolytic virotherapy, despite indications from clinical case reports suggesting a potential association between VZV infection and cancer remission.Methods Here, we constructed oncolytic VZV candidates based on the vaccine strain vOka and the laboratory strain Ellen. These newly engineered viruses were subsequently assessed for their oncolytic properties in the human MeWo melanoma xenograft model and the mouse B16-F10-nectin1 melanoma syngeneic model.Results In the MeWo xenograft model, both vOka and Ellen exhibited potent antitumor efficacy. However, it was observed that introducing a hyperfusogenic mutation into glycoprotein B led to a reduction in VZV’s effectiveness. Notably, the deletion of ORF8 (encodes viral deoxyuridine triphosphatase) attenuated the replication of VZV both in vitro and in vivo, but it did not compromise VZV’s oncolytic potency. We further armed the VZV Ellen-ΔORF8 vector with a tet-off controlled mouse single-chain IL12 (scIL12) gene cassette. This augmented virus was validated for its oncolytic activity and triggered systemic antitumor immune responses in the immunocompetent B16-F10-nectin1 model.Conclusions These findings highlight the potential of using Ellen-ΔORF8-tet-off-scIL12 as a novel VZV-based oncolytic virotherapy.